2020
DOI: 10.7554/elife.58349
|View full text |Cite
|
Sign up to set email alerts
|

Expandable and reversible copy number amplification drives rapid adaptation to antifungal drugs

Abstract: Previously, we identified long repeat sequences that are frequently associated with genome rearrangements, including copy number variation (CNV), in many diverse isolates of the human fungal pathogen Candida albicans (Todd et al., 2019). Here, we describe the rapid acquisition of novel, high copy number CNVs during adaptation to azole antifungal drugs. Single-cell karyotype analysis indicates that these CNVs appear to arise via a dicentric chromosome intermediate and breakage-fusion-bridge cycles that are repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(153 citation statements)
references
References 188 publications
(274 reference statements)
7
146
0
Order By: Relevance
“…Interestingly, a recent study revealed that the copy number of CRZ1 was correlated with the occurrence of FCL tolerance in C. albicans isolates exposed to FLC. Assuming that CRZ1 gene copy number may be correlated with increased expression, this study corroborates with our observations ( Todd and Selmecki, 2020 ). How CRZ1 overexpression mediates azole tolerance is still unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a recent study revealed that the copy number of CRZ1 was correlated with the occurrence of FCL tolerance in C. albicans isolates exposed to FLC. Assuming that CRZ1 gene copy number may be correlated with increased expression, this study corroborates with our observations ( Todd and Selmecki, 2020 ). How CRZ1 overexpression mediates azole tolerance is still unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this, the PR mutants grew better and displayed a transcriptomic profile similar to WT cells. These results are also interesting in that genomic analysis revealed that the different classes of PR mutants showed distinct mechanisms for mutation of BCY1 or deletion of parts of the left arm of chromosome 2 (Extended Data Table 1), which underscore how the plasticity of the C. albicans genome enables it to adapt to different kinds of stress from mutations or antifungal drugs 35, 36, 59, 60 .…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, it is more and more evident that aneuploidy can actually also be beneficial for adaptation, especially when gene expression issues are resolved [ 67 ]. Indeed, aneuploidies were shown to drive the adaptation to different types of environmental stress, including limiting nutrients, high ethanol concentration, heat shock, oxidative stress, endoplasmic reticulum stress, and drug resistance [ 31 , 92 , 93 , 155 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ]. In addition, aneuploidy has been shown to help suppress certain genetic mutations such as telomerase insufficiency [ 202 , 203 ], cytokinesis perturbation [ 91 ], disruption of essential nucleoporin genes [ 204 ] and loss of a small ubiquitin-related modifier protease [ 205 ].…”
Section: Aneuploidy and Segmental Duplications: A “Quick Fix” For Evolutionary Adaptation?mentioning
confidence: 99%